Dual- versus single-energy CT-angiography imaging for patients undergoing intracranial aneurysm repair - Abdulazim, Amr Nabil; Hänggi, Daniel; Etminan, Nima (Cerebrovascular diseases, 2017)
Background: The invasiveness and risk of thromboembolic complications of catheter angiography underline the need for alternative imaging modalities in patients following intracranial aneurysm (IA) repair. However, the overall image quality of existing noninvasive imaging modalities, such as single-energy CT angiography (SE-CTA), compromises its value in this respect. Objective: We prospectively investigated the value of a novel dual-energy CTA (DE-CTA) scanner and algorithm for assessing the degree of occlusion and parent vessel patency in patients following IA repair. Methods: A prospective cohort of 17 patients underwent DE-CTA imaging following surgical or endovascular IA repair. This dataset was matched with an identical historical cohort of 17 patients, who underwent IA repair and SE-CTA imaging. Beam-hardening artifacts, as a measure for objective imaging quality were analyzed based on the volume of a prolate ellipsoid, whereas subjective imaging quality at the IA site and corresponding parent vessels was rated by 2 independent neuroradiologists on a scale from 4 (excellent, no artifacts) to 1 (poor, severe artifacts). Results: Objective DE-CTA image quality was markedly higher, compared to SE-CTA in patients undergoing surgical (0.77 ± 0.23 vs. 10.91 ± 1.88 mL, respectively; p < 0.001) or endovascular (32.36 ± 10.62 vs. 107.63 ± 24.51 mL, respectively; p = 0.026) IA repair. Subjective image quality for DE-CTA was significantly improved compared to SE-CTA in the surgical group but not in the endovascular group. The calculated dose values for DE-CTA in our study remain markedly below the legally required radiation dose limits. Conclusion: The imaging quality of DE-CTA, especially for patients undergoing surgical IA repair, is distinctly superior, compared to SE-CTA imaging. Therefore, DE-CTA may serve as a noninvasive alternative for assessing the IA occlusion rate and parent vessel patency.
Gesehen am 29.03.2018